Historia i współczesność "Bibliotekarza Lubuskiego" pisma zielonogórskiej Wojewódzkiej i Miejskiej Biblioteki Publicznej im. Cypriana Norwida = History and present day of "Bibliotekarz Lubuski" ("Lubuski Librarian") - Rudiak, Robert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article documents the 60-year history of the magazine published by The Cyprian Norwid Regional and City Public Library in Zielona Góra, which appeared as a library periodical in 1958, initially as "Biuletyn Informacyjno-Bibliograficzny" ("The Information and Bibliographic Bulletin"), then as "Biuletyn Informacyjny WiMBP" ("The Library Information Bulletin"), "Kultura Lubuska" ("Lubusz Culture") from 1959 to 1960 and "Bibliotekarz lubuski" ("Lubuski Librarian")from 1961 to 1971. After a ten-year break, an unsuccessful attempt to reactivate the magazine was made. It appeared only in 1981, and due to the difficult economic and social situation in Poland as well as the martial law, its publication was discontinued. Again, the journal was reactivated after another 12 year-break and it came out as "Biuletyn Informacyjny SBP" ("SBP Information Bulletin") from 1993 to 1995, and since 1996 it has been published as "Bibliotekarz Lubuski". Since then, the periodical has been published as a semi-annual magazine. During the years 1958-2018 a total of 136 issues were published of the Zielona Góra Library magazine ? 12 issues of "Biuletyn Informacyjno-Bibliograficzny" and "Biuletyn Informacyjny WiMBP", 24 numbers of "Kultura Lubuska", 46 numbers of "Bibliotekarz Lubuski", 7 issues of "Biuletyn Informacyjny SBP" and 47 issues of the current "Bibliotekarz Lubuski", published from 1996 (data till the end of 2018).
Keywords: Bibliotekarz Lubuski (czasopismo); Wojewódzka i Miejska Biblioteka Publiczna im. C. Norwida w Zielonej Górze; czaspoisma bibliotekarskie; Bibliotekarz Lubuski (magazine); The Cyprian Norwid Regional and City Public Library in Zielona Góra; library magazines